2017
DOI: 10.1016/j.cmi.2016.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Benzylpenicillin plus an aminoglycoside versus meropenem in neutropenic lymphoma and leukaemia patients with a suspected bacterial infection: a randomized, controlled trial

Abstract: Clinical success was more common in FN patients randomized to meropenem compared with the patients randomized to benzylpenicillin plus an aminoglycoside. The all-cause fatality was higher among the patients given benzylpenicillin plus an aminoglycoside.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Mistrust could be the result of biased information. For example, a randomized controlled trial on adult patients with febrile neutropenia performed in Norway demonstrated significantly higher failure rates and mortality in patients empirically treated with benzylpenicillin and an aminoglycoside relative to carbapenems [30]. On the other hand, a retrospective study from Norway comparing children with febrile neutropenia receiving either benzylpenicillin or ampicillin and an aminoglycoside or a regimen based on third-generation cephalosporins revealed no significant difference in clinical outcome [31].…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Mistrust could be the result of biased information. For example, a randomized controlled trial on adult patients with febrile neutropenia performed in Norway demonstrated significantly higher failure rates and mortality in patients empirically treated with benzylpenicillin and an aminoglycoside relative to carbapenems [30]. On the other hand, a retrospective study from Norway comparing children with febrile neutropenia receiving either benzylpenicillin or ampicillin and an aminoglycoside or a regimen based on third-generation cephalosporins revealed no significant difference in clinical outcome [31].…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…65,66 The most frequent bacteria causing infections in acute leukemia patients are summarized in Table 1. [67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84] Previous studies have documented bloodstream infections in 15-38% of patients with hematological malignancies. 62,[85][86][87] In Europe and the US, Gramnegative organisms were the most predominant pathogens during the 1970s and the 1980s, followed by a shift toward Gram-positive organisms.…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…The main antibiotics and their characteristics are presented in Table 2. 50,67,68,70,71,[73][74][75][76][77][78][79][80][81][101][102][103][104][105][106][107][108][109] Adjuvant sepsis-treatment as fluids therapy is important in sepsis treatment, although secondary to antibiotic treatment and adequate source control. 110 However, optimization of hemodynamically unstable patients, including volume support supplemented with a vasopressor, inotropic and transfusion of red blood cells (RBCs) in case of persistent hypo-perfusion has the potential to reduce morbidity and mortality and can prolong survival and improve quality of life.…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Carbapenems should not be used for initial, empiric therapy in febrile neutropenia. When the study [2] was started in 2006, we were concerned that broad-spectrum antibiotics were being used unnecessarily, also in Norway [3]. The focus of the study was an assessment of the traditional Norwegian antibiotic regimen of benzylpenicillin plus an aminoglycoside.…”
Section: Dear Sirmentioning
confidence: 99%